Demand Response Cost vs Cost of Energy Purchased in the Wholesaler Market - Castro, Rafael (2018)
ith the increase of the production of electricity through renewable sources and the with the growing penetration of distributed production (decentralized production) as well as the implementation of the concept of Demand Response (DR), it is progressively possible to operate distribution networks autonomously. The aim of the DR concept it is to reduce consumption in exchange of an incentive or remuneration, when requested. This article studies the implementation of DR in a distribution network in order to verify what type of remuneration (tariff) suits best, from the point of view of the network operator.